The association between healthy lifestyle behaviors and health-related quality of life among adolescents - José J. Muros; Federico Salvador Pérez; Félix Zurita Ortega; Vanesa M. Gámez Sánchez; Emily Knox (Jornal de Pediatria)
Abstract Objective: The aim of this research was to examine the association between body mass index, physical activity, adherence to the Mediterranean diet, and health-related quality of life in a sample of Spanish adolescents. Method: The study involved 456 adolescents aged between 11 and 14 years. They completed questionnaires on the Mediterranean diet (KIDMED), physical activity (Physical Activity Questionnaire for Older Children [PAQ-C]), and quality of life (KIDSCREEN-27). Body mass index was calculated. Hierarchical linear regression analyses were used to determine whether health-related quality of life could be predicted by the measured variables. The variables were analyzed in a stepwise manner, with Mediterranean diet entered in the first step, body mass index in the second, and physical activity in the third. Results: Mediterranean diet accounted for 4.6% of the variance in adolescent's health-related quality of life, with higher adherence to the Mediterranean diet predicting higher health-related quality of life-scores. Body mass index accounted for a further 4.1% of the variance, with a higher body mass index predicting lower health-related quality of life scores. Finally, physical activity explained an additional 11.3% of the variance, with a higher level of physical activity being associated with higher health-related quality of life scores. Together, these variables explained 20% of the variance in the adolescents' health-related quality of life. Conclusions: Physical activity, body mass index, and adherence to the Mediterranean diet are important components to consider when targeting improvements in the health-related quality of life of adolescents, with physical activity representing the component with the greatest influence.